Ecological Aspects of Fiddler Crab (Uca spp) in the Mangrove Ecosystem of Poka Village, Inner Ambon Bay - Lewerissa, Yona A.; Hulopi, Mahriyana (Agrikan Jurnal Agribisnis Perikanan, 2023)
The condition of the degraded PLTD Poka mangroves can affect the condition of fiddler crabs. For this reason, the study aims to invent fiddler crab species, analyze the density and frequency of occurence, and determine the ecological index of fiddler crabs in the mangrove ecosystem of PLTD Poka Inner Ambon Bay. Data collection of fiddler crabs (Uca spp.) in the PLTD Poka mangrove ecosystem in June–August 2023 using the purposive sampling method at all five stations The results of the study found four species of fiddler crabs, namely Uca mjoebergi, Uca perplexa, Uca vocans, and Uca vomeris, at five stations in the Poka mangrove ecosystem, which belong to one class, one family, and one genus. Overall, the species with the highest density was Uca perplexa, while the species with the lowest density was U. vomeris, with the highest density at station 5 and the lowest density at station 2. The highest frequency of occurence is represented by Uca perplexa, while the lowest is in the species Uca mjoebergi. The diversity of fiddler crabs in the Poka mangrove ecosystem is in the medium category, with species compatibility in a balanced state with low species dominance.